If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6.3=x+1.8
We move all terms to the left:
6.3-(x+1.8)=0
We get rid of parentheses
-x-1.8+6.3=0
We add all the numbers together, and all the variables
-1x+4.5=0
We move all terms containing x to the left, all other terms to the right
-x=-4.5
x=-4.5/-1
x=4+0.5/1
| 2(-6b-1)=-2-12b | | 39=f–10+ 45 | | 13.7p-16.43=19p | | 12/10=x/60 | | 3x-8=16 | | 11+6t=6t+9+2 | | (9)(3x)-1=0 | | 5-2l=-5 | | 34+7l=111 | | 15-d=23 | | 4=v/3-1 | | t-1,t=7 | | -3x+8=-5x-18 | | 3-(x+4)=5x+8 | | -17k-20=2(-9k-10)+16 | | 19k+2=21 | | 10=u-1 | | -13u+3=-10u+12 | | 19k+2=22 | | 4n-8=3n+8 | | T-4=5t+3t-32 | | 1(10k-16)+11=-2 | | 2(x+4)=16-6x* | | y+12=42 | | 80=0.25x(50+45) | | F(n)=24 | | 1=3+p/8 | | f/6-20=-22 | | r-76=67 | | 6+14n=-14-17+14n | | 4y,y=3 | | x-4x3=24 |